Relationship between human resource professionals' competencies, human resource professionals' roles and organizational performance - Choi, Sang Long, 1970-; Salmiah Mohamad Amin, supervisor; Wan Khairuzzaman Wan Ismail, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2011)
Thesis (Doktor Falsafah (Pengurusan)) - Universiti Teknologi Malaysia, 2011